Influence of cryosoaking period on wear characteristics and surface topography of M35 tool steel. (3rd July 2018) - Dhokey, N. B.; Lalge, P. K.
ABSTRACT: Cryogenic treatment affects tool steels wherein alteration in microstructural features like phases, uniform precipitation of carbides is observed. In this work, improvement in wear resistance of cryotreated material with microstructural features and surface roughness of material has been correlated. Samples of AISI M35 steel were hardened at 1200°C, followed by triple tempering at 555°C in the salt bath, subsequently subjected to cryogenic treatment at minus 185°C for varying cryosoaking period (4–32 h) followed by soft tempering at 100°C. Such samples were characterized for hardness, microstructure, carbide density, wear rate and surface roughness. A correlation of carbide density and roughness has been established with wear resistance.